2006
DOI: 10.1213/01.ane.0000223684.76783.bf
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to Propofol’s Sedative Effect in Mechanically Ventilated Rabbits

Abstract: Propofol is commonly used for the sedation of critically ill patients undergoing mechanical ventilation. These patients may develop tolerance during long-term administration. Here, we describe the development of tolerance to propofol's sedative effect in rabbits during prolonged mechanical ventilation. Six healthy male New Zealand White rabbits were endotracheally intubated and received propofol by continuous IV infusion to maintain sedation for 48 h. The propofol infusion rate (IR) was adjusted to maintain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 13 publications
2
17
0
4
Order By: Relevance
“…Histological examination revealed no inflammation of the heart, and immunohistochemistry revealed little TNF-α staining. These results demonstrated that the lipid solvent caused few catastrophic manifestations of PRIS, which is consistent with previous studies [16,21] .…”
Section: Discussionsupporting
confidence: 93%
“…Histological examination revealed no inflammation of the heart, and immunohistochemistry revealed little TNF-α staining. These results demonstrated that the lipid solvent caused few catastrophic manifestations of PRIS, which is consistent with previous studies [16,21] .…”
Section: Discussionsupporting
confidence: 93%
“…34 To keep the animals anesthetized for long periods without changes in muscle physiology, we selected a previously described method that uses a continuous infusion of propofol. 32,35 To control respiratory acidosis generated by the spontaneous ventilation, the animals were intubated and mechanically ventilated. Respiratory rates were manually adjusted to keep pH and pCO 2 physiologic.…”
Section: Discussionmentioning
confidence: 99%
“…Ancak gruplar kendi içlerinde değerlendirildiklerinde; Grup S'de 8.-12. saat, Grup SK'de ise 6.-12. saatler arasın-da sevofluranın uygulanma yüzdesinin bazal değerlere göre istatistiksel açıdan anlamlı olarak daha yüksek olduğu tespit edildi. Ypsilantis ve arkadaşlarının yaptığı ve uzamış sevofluran inhalasyonu ve propofol infüzyonlarının tavşanlar üze-rindeki etkilerinin incelendiği çalışmada da (17,29) bizim çalışmamızın sonuçlarına benzer olarak deney sırasında istenilen sedasyon seviyelerine ulaşabilmek için hayvanlara uygulanan sevofluran yüzdesinin arttırılması (%1'den %4'e) gerektiği tespit edilmiştir. Ancak bizim çalışmamızda istenilen sedasyon seviyesi ve BİS değerlerine ulaşabilmek için daha yüksek sevofluran yüzdelerine ihtiyaç duyulduğu dikkati çekmiştir.…”
Section: Bulgularunclassified
“…Çalışmamızın sonuçlarına benzer olarak tavşanlarda propofolün sedatif etkisine karşı gelişen toleransın incelendiği bir çalışmada (29); istenilen sedasyon seviyesine ulaşa-bilmek için gerekli propofol infüzyon hızının zaman ile arttı-ğı belirtilmiştir. Yazarlar gruplardaki tüm hayvanlarda propofolün sedatif etkisine infüzyona başladıktan sonraki 1-2 saat içinde tolerans gelişerek sistemik klirens hızının arttığı-nı ve istenilen sedasyon seviyesinin sağlanabilmesi için uzun süre yüksek infüzyon hızlarına ihtiyaç olduğunu fakat daha sonra muhtemelen ilacın yağ dokusunda birikimine ve karaciğer metabolik etkinliğinin aşılmasına bağlı olarak ihtiyaç duyulan propofol dozlarının kademeli olarak azaldığını belirtmişlerdir.…”
Section: Bulgularunclassified
See 1 more Smart Citation